Establishing limits of the housing rights realization by means of legal restrictions - Марценко, Н. С. (Theory and practice of jurisprudence, 2016)
Analysis of the concept of limits of their housing rights realization and legal restrictions. The author draws attention to the important role of legal restrictions to establish limits of housing rights realization and the need for strict regulation because of high social importance the object of this rights - house. Emphasized that the exercise of subjective housing law should always be within certain limits, which in the cases stipulated by law can clearly limit.